2019
DOI: 10.1109/jphot.2019.2939088
|View full text |Cite
|
Sign up to set email alerts
|

Mode Sensitivity Analysis of Subwavelength Grating Slot Waveguides

Abstract: In this paper, we investigate the mode sensitivity (S mode) of subwavelength grating slot (SWGS) waveguides. S mode is an important parameter in various waveguide-based photonic circuits such as sensors, modulators, and thermally-controlled devices. It is a measure of the sensitivity of the waveguide effective index towards the refractive index perturbations in the cladding medium. The SWGS waveguide exhibits high mode sensitivity, as it combines sensitivity enhancement features of both slot and subwavelength … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…arm, Δφ is an constant, thus our proposed MZI sensor can enhance the sensitivity by optimizing the reference arm length while maintain a fixed DR. This is different from most sensitivity enhancement schemes in which the Δφ is increased by enhancing the light-analyte interaction length or degree of the MZI sensor [11][12][13][14]. We followed the designed parameters to fabricate the proposed device.…”
Section: Principle and Designmentioning
confidence: 99%
See 2 more Smart Citations
“…arm, Δφ is an constant, thus our proposed MZI sensor can enhance the sensitivity by optimizing the reference arm length while maintain a fixed DR. This is different from most sensitivity enhancement schemes in which the Δφ is increased by enhancing the light-analyte interaction length or degree of the MZI sensor [11][12][13][14]. We followed the designed parameters to fabricate the proposed device.…”
Section: Principle and Designmentioning
confidence: 99%
“…Over the past decades, optical waveguide liquid refractive index (RI) sensors have received more and more attention as an increasingly important tool in biochemical analysis applications by virtue of their unique advantage enabling high-sensitive, real-time, and label-free detection [1]. To date, various optical waveguide liquid RI sensors employing various configurations, including ring resonator [2][3][4], grating-assisted directional coupler [5], grating [6], Young interferometer [7], multimode interferometer [8], and Mach-Zehnder interferometer (MZI) [9][10][11][12][13][14][15][16][17][18], have been proposed. Among them, the MZI-based sensors have distinctive advantages of structural simplicity and diversity, design flexibility, and the potential of ultra-high sensitivity, making them an important and promising type.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2018, Luan et al proposed and demonstrated a “multi‐box” microring biosensor as a fusion of SWG and slot structures (see Figure 7k) with one of the characterized record highest sensitivities to bulk refractive index change of ≈580 nm per RIU and surface sensitivity of ≈1900 pm nm −1 in a standard bio‐sandwich assay. [ 178,179 ] Very recently, the concept of “multi‐box” waveguide has been further investigated with the incorporation of Bragg grating [ 180 ] and MZI‐based [ 181 ] sensing structures.…”
Section: Emerging Sensor Designs and Biosensing Strategiesmentioning
confidence: 99%
“…S mode is an essential parameter which should be taken into consideration while designing sensing devices [31]. S mode is evaluated for the geometric parameters of the WG and is calculated by using the following expression:…”
Section: Mode Sensitivity Analysis Of Te and Tm Hybrid Modementioning
confidence: 99%